2014
DOI: 10.1094/phyto-12-13-0348-r
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Transmission of Asparagus virus 2 (AV-2) May Facilitate Mixed Infection by Two AV-2 Isolates in Asparagus Plants

Abstract: Asparagus virus 2 (AV-2) is a member of the genus Ilarvirus and thought to induce the asparagus decline syndrome. AV-2 is known to be transmitted by seed, and the possibility of pollen transmission was proposed 25 years ago but not verified. In AV-2 sequence analyses, we have unexpectedly found mixed infection by two distinct AV-2 isolates in two asparagus plants. Because mixed infections by two related viruses are normally prevented by cross protection, we suspected that pollen transmission of AV-2 is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Several ilarviruses and other members of family Bromoviridae were shown to be horizontally transmitted through pollen (Gilmer and Way 1960; George and Davidson 1963; Sdoodee and Teakle 1988; Greber et al 1991; Mink 1993; Sdoodee and Teakle 1993; Aparicio et al 1999; Card et al 2007; Kawamura et al 2014; Jaspers et al 2015). In some cases, ilarviruses were also reported to be associated with pollen surfaces or exine (Hamilton 1977; Digiaro and Savino 1992; Fetters et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several ilarviruses and other members of family Bromoviridae were shown to be horizontally transmitted through pollen (Gilmer and Way 1960; George and Davidson 1963; Sdoodee and Teakle 1988; Greber et al 1991; Mink 1993; Sdoodee and Teakle 1993; Aparicio et al 1999; Card et al 2007; Kawamura et al 2014; Jaspers et al 2015). In some cases, ilarviruses were also reported to be associated with pollen surfaces or exine (Hamilton 1977; Digiaro and Savino 1992; Fetters et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Shimura et al (2013) further revealed low genetic variability among AV-2 isolates and clarified the function of the 2b protein of AV-2 as an RNA suppressor. Subsequently, Kawamura et al (2014) suggested the involvement of pollen transmission in co-infection by two AV-2 isolates in plants.…”
Section: Realm Riboviria Phylum Duplornaviricota Kingdom Orthornavira...mentioning
confidence: 99%
“…Asparagus virus 2 (AV2) is a member of ilarvirus subgroup 2. AV2 is transmitted by seeds and pollen, but also mechanically by sap-contaminated tools during harvesting (Jaspers et al, 1999; Kawamura et al, 2014). It was shown that AV2 is capable of infecting by sap inoculation at least twenty-seven species of herbaceous plants in seven families, including Chenopodium quinoa and various tobacco species, which makes AV2 a good model for ilarvirus research (Fujisawa et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that AV2 is capable of infecting by sap inoculation at least twenty-seven species of herbaceous plants in seven families, including Chenopodium quinoa and various tobacco species, which makes AV2 a good model for ilarvirus research (Fujisawa et al, 1983). Despite the fact that AV2-infected asparagus plants do not display visible symptoms, infection leads to a significant reduction in yield resulting in serious economic losses (Jaspers et al, 1999; Kawamura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%